COMPARATIVE TOXICITY STUDY OF CHLOROQUINE AND HYDROXYCHLOROQUINE ON ADULT ALBINO RATS - El Shishtawy, Mohamad A.; Hassan, Khodor Haidar; Ramzy, Ragaee; Berri, Fadwa; Mortada, Mohamad; Nasreddine, Salam; Ezzedine, Mohamad (European Scientific Journal, ESJ, 2015)
Expanded use of Chloroquine and hydroxychloroquine drugs for non-malarial disease entities has resulted in prolonged duration of therapy and higher daily dosages leading to cumulative doses greater than those used in antimalarial therapy. The aim of the study is to evaluate and compare the toxic effects of chloroquine and hydroxychloroquine on different organs of albino rats. The study was conducted on 60 normal albino rats divided into 3 groups, the 1st group is the control group that received only distilled water, the 2nd and the 3rd group were given a single daily oral doses equivalent to 1/10th of LD50 chloroquine and hydroxychloroquine respectively. Assessment of liver and kidney functions, and histopathological changes in liver, kidney, and heart in different groups was done. The chloroquine treated group showed significant elevation of serum glutamic pyruvic transaminase (SGPT), serum glutamic oxaloacetic transaminase (SGOT), alkaline phosphatase (ALP), total bilirubin (TB), serum creatinine-urea (Cr-U), Creatine Kinase-MB, C-reactive protein and Malonic dialdehyde levels as compared to control and hydroxychloroquine treated group. The histopathological evaluation showed marked hydropic degeneragtion, vascular congestion, interstitial hemorrhage, and necrosis in the liver, kidney and heart of chloroquine treated group, while hydroxychloroquine treated group showed mild congestion and slight cellular degeneration. Thus, hydroxychloroquine is less toxic and physicians should prescribe it better than chloroquine. Chloroquine if prescribed for therapeutic uses should be taken for short periods.